A Giant Problem: The Influence of the Chicago School on Australian Competition Law, Economic Dynamism and Inequality. (December 2019) - Triggs, Adam; Leigh, Andrew
Australia has a competition problem: there is not enough of it. Our industries are concentrated. Our markets show signs of weak competition. The way Australia's courts, parliamentarians and regulators think about competition is partly to blame. Although it has been less influential in Australia than in the United States, the Chicago School's views on competition have shaped our laws, policies and enforcement practices. The Chicago School views market concentration as a virtue more than a vice. The School contended that barriers to entry are negligible, market power is temporary, most mergers are good, vertical restraints and predatory pricing are either benign or efficient. The growing body of research and experience, however, shows that the Chicago School's faith in the ability of markets to self-correct and deliver competitive outcomes was misplaced. There is a strong progressive case for repositioning how we think about competition. Focusing more on the competitive process, the structure of markets and the incentives those structures create for firms will play an important role in reducing inequality.